Aberrant expression of E-cadherin and beta-catenin proteins in placenta of bovine embryos derived from somatic cell nuclear transfer - Kohan-Ghadr, H. R.; Smith, L. C.; Arnold, D. R. [UNESP]; Murphy, B. D.; Lefebvre, R. C. (CSIRO Publishing, 2012)
Abnormal placental development is common in the bovine somatic cell nuclear transfer (SCNT)-derived fetus. In the present study, we characterised the expression of E-cadherin and beta-catenin, structural proteins of adherens junctions, in SCNT gestations as a model for impaired placentation. Cotyledonary tissues were separated from pregnant uteri of SCNT (n - 6) and control pregnancies (n - 8) obtained by artificial insemination. Samples were analysed by western blot, quantitative RT-PCR (qRT-PCR) and immunohistochemistry. Bovine trophectoderm cell lines derived from SCNT and control embryos were analysed to compare with the in utero condition. Although no differences in E-cadherin or beta-catenin mRNA abundance were observed in fetal tissues between the two groups, proteins encoded by these genes were markedly under-expressed in SCNT trophoblast cells. Immunohistochemistry revealed a different pattern of E-cadherin and total beta-catenin localisation in SCNT placentas compared with controls. No difference was observed in subcellular localisation of dephosphorylated active-beta-catenin protein in SCNT tissues compared with controls. However, qRT-PCR confirmed that the wingless (WNT)/beta-catenin signalling pathway target genes CCND1, CLDN1 and MSX1 were downregulated in SCNT placentas. No differences were detected between two groups of bovine trophectoderm cell lines. Our results suggest that impaired expression of E-cadherin and beta-catenin proteins, along with defective beta-catenin signalling during embryo attachment, specifically during placentation, is a molecular mechanism explaining insufficient placentation in the bovine SCNT-derived fetus.
Keywords: adhesion molecules placenta; Bovine; trophoblast